Development of a Web-Based Arabic Competency Test for Indonesian Speakers as a Reference for Measuring Arabic Proficiency Levels of Undergraduate and Graduate Students in Arabic Language Education at Universitas Negeri Jakarta - Arifa, Fatwa; Kamal, Muhammad; Tajuddin, Shafruddin; Bahtiar, Ihwan Rahman; Masyitoh, Siti; Yani, Achmad (Arabiyatuna: Jurnal Bahasa Arab, 2025)
This study aims to establish Arabic language proficiency standards through a TOAFL-based competency evaluation model that is recognised both nationally and internationally. The research employed a Research and Development (R&D) approach following the Gall and Borg model. Data analysis ensured validity and reliability through prolonged engagement, persistent observation, and triangulation. The prototype developed in this study measures three key aspects of Arabic proficiency: listening comprehension, structure and written expression, and reading comprehension. Each aspect consists of several sections that assess different linguistic skills through 150 multiple-choice questions. The study also produced a question bank containing structured Arabic test materials designed for standardised assessment. Test scores are processed using a tabulation system that converts correct and incorrect responses into numerical values to generate total scores. The outcome of this research is a prototype of a standardised web-based Arabic language competency test model for Indonesian speakers, which can be used as a valid instrument for assessing Arabic language proficiency at the undergraduate and master’s levels.